Iagttagelser fra en Reise i Storbritanien. Foredrag, den 31te Januar 1866. - la Cour, Albert (Tidsskrift for Landøkonomi, 2018)
Iagttagelser fra en Reise i Storbritanien. Foredrag, den 31te Januar 1866.